Hermeneutical Foundations of Islamic Education: A Quranic and Prophetic Perspective on Learning - Asman Asman; Woro Yustia Pratiwi; Bambang Sismedi Saputro; Muhammad Muhammad; Andri Nirwana (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
The issue of Islamic education has always been an intriguing topic of scholarly inquiry. The use of hermeneutics as the foundational basis of Islamic education is grounded in the Qur’an and prophetic teachings. The objective of this study is to analyze the extent to which the hermeneutic method can serve as a foundation for Islamic education. This research employs a qualitative method with a library research approach. The data sources consist of both primary and secondary materials. Primary data were obtained from key reference books, while secondary data were drawn from relevant journals, books, magazines, and other documents related to this research. The data were analyzed using content analysis. The findings indicate that Islamic education requires the integration of cognitive, affective, and spiritual dimensions, all of which aim to bring human beings closer to God and to actualize their human potential. Thus, Qur’anic and prophetic hermeneutics offer a dynamic conceptual framework for understanding Islamic education as a process of meaning-making rather than merely a transfer of knowledge.